Electrocardiographic findings in athletes: the prevalence of left ventricular hypertrophy and conduction defects - Langdeau, J. B.; Blier, L.; Turcotte, H.; O'Hara, G.; Boulet, L. P. (Canadian Journal of Cardiology, 2001)
OBJECTIVES: To determine whether there are electrocardiographic differences or distinctive abnormalities between athletes and sedentary subjects, and to verify the relationship between vagal activity measured by heart rate variability (SD of all normal-to-normal intervals [SDNN]) and possible electrocardiographic abnormalities. SUBJECTS AND METHODS: Resting electrocardiograms and heart rate variability measurements were performed separately during a single visit on 100 athletes and 50 nonathlete control subjects aged 18 to 55 years. The athletes were from the following various sports disciplines: long-distance running, mountain biking, cross-country skiing, biathlon, speed skating, swimming and triathlon. RESULTS AND CONCLUSIONS: There were significantly longer RR intervals, PR intervals and QT intervals in athletes than in control subjects (all P<0.05). The QRS complex and QTc did not show significant differences (both P>0.05). The prevalence of left ventricular hypertrophy (LVH) and incomplete right bundle branch block (IRBBB) was 10% and 7%, respectively, in athletes, but these conditions were absent in control subjects; among athletes, 2% presented with both conditions. LVH and IRBBB were more common among long-distance runners (six of 14 and four of 14, respectively) and could be attributed to normal, long term adaptation to intense, repeated exercise. LVH was related to age (P=0.04), whereas IRBBB was influenced by the number of years of training in the respective sports discipline (P=0.03). The mean SDNN value was significantly more elevated in athletes (P=0.0001), reflecting a higher parasympathetic tone than in sedentary control subjects. However, there was no relationship between vagal activity and LVH or IRBBB (both P>0.05).